RANCANG BANGUN BATTERY CHARGE CONTROLLER DUAL SUMBER PLTS DAN PLN SEBAGAI SUPLAI CHARGER LAPTOP - Andi Gunawan; Cecep E Rustana; Iwan Sugihartono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The purpose of this research is to make a device battery charge controller with dual energy sources, that is Solar Power Plant as a primary energy source and PLN (State Electricity Company) as a backup energy source. Sources of energy used is stored in two batteries which are controlled by the microcontroller Arduino Mega 2560. Microcontroller used to control a switch of two battery when charging and to prevent overcharging the battery. Besides, microcontroller is also used to assign which batteries will be used to supply the laptop charger, then to removal the resources to PLN when both batteries at the discharge condition. Voltage and current output charger controller for supply laptop charger are 20.12 volt and 2.67 ampere. Keywords: dual energy, charge controller, microcontroller, laptop.